New RP-HPLC Method Development and Validation for Dorzolamide in Ophthalmic Dosage Form - Boovizhikannan Thangabalan; Getu Kahsay; Tadele Eticha (Journal of Analytical Methods in Chemistry)
A reversed phase liquid chromatographic method with UV detection at 254 nm for dorzolamide assay in ophthalmic solutions was developed and validated. Chromatographic separation was achieved on a Zorbax SB C18 (250 mm × 4.6 mm, 5 µm) column kept at 30°C with an isocratic mixture of mobile phase (phosphate buffer, pH 2.5, and acetonitrile, 90 : 10 v/v) at a flow rate of 0.8 mL/min. The method was validated for its specificity, linearity, accuracy, precision, limit of detection, limit of quantification, and robustness based on ICH guidelines. The validation studies revealed satisfactory results. The proposed method has been applied for the quantification of dorzolamide in commercial samples. The developed method is fast, simple, specific, accurate, and sensitive, hence can be applied for routine quality control analysis of dorzolamide in pharmaceutical dosage form.